Functional and Structural Brain Damage in Friedreich's Ataxia - Vavla, Marinela; Arrigoni, Filippo; Nordio, Andrea; De Luca, Alberto; Pizzighello, Silvia; Petacchi, Elisa; Paparella, Gabriella; D'Angelo, Maria Grazia; Brighina, Erika; Russo, Emanuela; Fantin, Marianna; Colombo, Paola; et al. (Frontiers in Neurology, 2018)
Friedreich's ataxia (FRDA) is a rare hereditary neurodegenerative disorder caused by a GAA repeat expansion in the FXN gene. There is still no cure or quantitative biomarkers reliaby correlating with the progression rate and disease severity. Investigation of functional and structural alterations characterizing white (WM) and gray matter (GM) in FRDA are needed prerequisite to monitor progression and response to treatment. Here we report the results of a multimodal cross-sectional MRI study of FRDA including Voxel-Based Morphometry (VBM), diffusion-tensor imaging (DTI), functional MRI (fMRI), and a correlation analysis with clinical severity scores. Twenty-one early-onset FRDA patients and 18 age-matched healthy controls (HCs) were imaged at 3T. All patients underwent a complete cognitive and clinical assessment with ataxia scales. VBM analysis showed GM volume reduction in FRDA compared to HCs bilaterally in lobules V, VI, VIII (L>R), as well as in the crus of cerebellum, posterior lobe of the vermis, in the flocculi and in the left tonsil. Voxel-wise DTI analysis showed a diffuse fractional anisotropy reduction and mean, radial, axial (AD) diffusivity increase in both infratentorial and supratentorial WM. ROI-based analysis confirmed the results showing differences of the same DTI metrics in cortico-spinal-tracts, forceps major, corpus callosum, posterior thalamic radiations, cerebellar penduncles. Additionally, we observed increased AD in superior (SCP) and middle cerebellar peduncles. The WM findings correlated with age at onset (AAO), short-allelle GAA, and disease severity. The intragroup analysis of fMRI data from right-handed 14 FRDA and 15 HCs showed similar findings in both groups, including activation in M1, insula and superior cerebellar hemisphere (lobules V–VIII). Significant differences emerged only during the non-dominant hand movement, with HCs showing a stronger activation in the left superior cerebellar hemisphere compared to FRDA. Significant correlations were found between AAO and the fMRI activation in cerebellar anterior and posterior lobes, insula and temporal lobe. Our multimodal neuroimaging protocol suggests that MRI is a useful tool to document the extension of the neurological impairment in FRDA.